Analyzing Identity Storytelling for On-site Learning in Museums: A Comparative Study of 3 City Museums with an Identity Education Framework - Lei, Zhichao (International Journal of Advanced Corporate Learning (iJAC), 2024)
This research investigates the specific designs of on-site identity storytelling in city museums, made of three case studies with an Identity Education (IdEd) framework proposed in an early conference paper by the author. Conclusions of the case studies are reached on how the city museums take advantage of different contextual factors to engage the visitors of five motivational types, whether there is any gap between the target identity expected by the city and the identity narratives presented by the city museum, and if any, how huge the gap is. The subsequent discussion, comparing the three cases, makes this research a comparative study and provides suggestions for each city museum. In general, this research sets an example of how the IdEd framework could be applied to the evaluation of on-site learning materials and opportunities in museums, thereby helping better the instructional design on the part of curators and offering guidelines for observing the museum visitors’ learning experiences in future field studies with similar educational concerns.